2013
DOI: 10.1371/journal.pone.0053405
|View full text |Cite
|
Sign up to set email alerts
|

RNAP-II Molecules Participate in the Anchoring of the ORC to rDNA Replication Origins

Abstract: The replication of genomic DNA is limited to a single round per cell cycle. The first component, which recognises and remains bound to origins from recognition until activation and replication elongation, is the origin recognition complex. How origin recognition complex (ORC) proteins remain associated with chromatin throughout the cell cycle is not yet completely understood. Several genome-wide studies have undoubtedly demonstrated that RNA polymerase II (RNAP-II) binding sites overlap with replication origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…In addition, CTD truncation mutations show increased instability of minichromosomes 130 . More recent experiments have suggested that stalled Pol II elongation complexes recruit components of the origin replication complex (ORC) through interactions with the CTD 131 . This model is consistent with genome-wide mapping studies showing a correlation between Pol II promoters and ORC complexes 132 .…”
Section: Functional Analysis Of Ctd Mutantsmentioning
confidence: 99%
“…In addition, CTD truncation mutations show increased instability of minichromosomes 130 . More recent experiments have suggested that stalled Pol II elongation complexes recruit components of the origin replication complex (ORC) through interactions with the CTD 131 . This model is consistent with genome-wide mapping studies showing a correlation between Pol II promoters and ORC complexes 132 .…”
Section: Functional Analysis Of Ctd Mutantsmentioning
confidence: 99%
“…On one hand, transcription revealed some positive links with replication initiation, as highly transcribed genes were proposed to replicate earlier than lowly expressed genes (Fraser 2013). Furthermore, stalled RNA polymerase II (RNA Pol II) was involved in the recruitment of the ORC at the rDNA locus, and the activity of many replication origins depends on the presence of specific transcription factor binding sites (Knott et al 2012;Mayan 2013). On the other hand, active ARSs are excluded from annotated ORFs and tend to localize after 3 ′ -transcription terminators, suggesting that transcription and replication initiation do not coexist (Nieduszynski et al 2006).…”
mentioning
confidence: 99%
“…Recent ChIP analyses have shown a peak in RNAP‐II binding in the non‐coding regions of the ribosomal repeats of S. pombe (Mayan, ). The intergenic regions of the mammalian ribosomal gene tandem repeats also contain binding sequences for RNAP‐II transcription factors and coding sequences that are transcribed by polymerase II (CDC27).…”
Section: Discussionmentioning
confidence: 99%
“…In budding yeast, it is thought that the typical crescent‐shaped structure of the nucleolus is caused by anchorage of the nucleolus to the nuclear pore complex or to the nuclear membrane, and in support of this hypothesis several perinuclear proteins have been proposed to be responsible for tethering the locus to the membrane (Mekhail et al ., ). We previously demonstrated that RNAP‐II bound to the ribosomal DNA sequences is found primarily in a stalled ternary complex and that the stalled polymerase is involved in rDNA replication (Mayan, ) and mediates the interaction between the two intergenic non‐coding regions, which organizes the locus into two different domains of transcription (Mayan and Aragon, ). In this report, we found that in the absence of the largest subunit of RNAP‐II, Rpb1p, the nucleolus loses its distinctive half‐moon crescent shape.…”
Section: Introductionmentioning
confidence: 99%